An Adverse Outcome Pathway for Decreased Lung Function Focusing on Mechanisms of Impaired Mucociliary Clearance Following Inhalation Exposure - Luettich, Karsta; Sharma, Monita; Yepiskoposyan, Hasmik; Breheny, Damien; Lowe, Frazer J. (Frontiers in Toxicology, 2021)
Adverse outcome pathways (AOPs) help to organize available mechanistic information related to an adverse outcome into key events (KEs) spanning all organizational levels of a biological system(s). AOPs, therefore, aid in the biological understanding of a particular pathogenesis and also help with linking exposures to eventual toxic effects. In the regulatory context, knowledge of disease mechanisms can help design testing strategies using in vitro methods that can measure or predict KEs relevant to the biological effect of interest. The AOP described here evaluates the major processes known to be involved in regulating efficient mucociliary clearance (MCC) following exposures causing oxidative stress. MCC is a key aspect of the innate immune defense against airborne pathogens and inhaled chemicals and is governed by the concerted action of its functional components, the cilia and airway surface liquid (ASL). The AOP network described here consists of sequences of KEs that culminate in the modulation of ciliary beat frequency and ASL height as well as mucus viscosity and hence, impairment of MCC, which in turn leads to decreased lung function.